‘Eurasian’: Negotiating a postcolonial identity in everyday life in multicultural Australia - Barrett, Michelle Anne (Curtin University, 2014)
This thesis interrogates the ambiguous and complex understandings surrounding the term ‘Eurasian’, which has emerged in Australia as a political, cultural and social reality from the neighbouring South and Southeast Asian region. Participants’ narratives of migration and identity were examined in order to gain insight into how this particular ‘mixed race’ identity is understood and negotiated in everyday life, and how migration processes which include recreating senses of ‘home’ and belonging, have impacted on these understandings.